Beyond authority leadership in a changing world - Middleton, Julia (New York Palgrave Macmillian, 2007)
Through compelling ideas and examples, Beyond Authority argues that new leaders need to be confident to legitimise themselves and challenge old ways. They need to develop a leadership style that enables them to lead beyond the traditional boundaries and constraints of their organizations.
Includes bibliographical references and index.
Keywords: Leadership